(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
This article provides a detailed analysis of the sign-semasis of Arabic borrowings found in explanatory dictionaries compiled for the works of Alisher Navoi. These borrowings—lexemes that express personal and object-related attributes (such as moral and psychological traits, appearance, color, and taste)—are examined from lexical-semantic, lexical-syntactic, and stylistic perspectives. In addition, the paper explores the contextual dependence of positive and negative character traits and their adaptation to the Uzbek language system.